Viscoelastic and fatigue properties of model methacrylate-based dentin adhesives - Ye, Qiang; Kieweg, Sarah L.; Park, Jonggu; Marangos, Orestes; Misra, Anil S.; Spencer, Paulette; Singh, Viraj (My University, 2010)
The objective of the current study is to characterize the viscoelastic and fatigue properties of model methacrylate-based dentin adhesives under dry and wet conditions. Static, creep, and fatigue tests were performed on cylindrical samples in a 3-point bending clamp. Static results showed that the apparent elastic modulus of the model adhesive varied from 2.56 to 3.53 GPa in the dry condition, and from 1.04 to 1.62 GPa in the wet condition, depending upon the rate of loading. Significant differences were also found for the creep behavior of the model adhesive under dry and wet conditions. A linear viscoelastic model was developed by fitting the adhesive creep behavior. The developed model with 5 Kelvin Voigt elements predicted the apparent elastic moduli measured in the static tests. The model was then utilized to interpret the fatigue test results. It was found that the failure under cyclic loading can be due to creep or fatigue, which has implications for the failure criterion that are applied for these types of tests. Finally, it was found that the adhesive samples tested under dry conditions were more durable than those tested under wet conditions. © 2010 Wiley Periodicals, Inc.
Keywords: Creep; Dentin adhesive; Dry and wet; Fatigue; Prony series; S-N curves; Viscoelastic